2020
DOI: 10.1186/s12863-020-00946-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure and symbiotic profile of worldwide natural populations of the Mediterranean fruit fly, Ceratitis capitata

Abstract: Background The Mediterranean fruit fly, Ceratitis capitata, is a cosmopolitan agricultural pest of worldwide economic importance and a model for the development of the Sterile Insect Technique (SIT) for fruit flies of the Tephritidae family (Diptera). SIT relies on the effective mating of laboratory-reared strains and natural populations, and therefore requires an efficient mass-rearing system that will allow for the production of high-quality males. Adaptation of wild flies to an artificial la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 70 publications
(128 reference statements)
2
25
0
Order By: Relevance
“…Two of the private haplotypes (M005 and M008) for the region only differed by two and three bases respectively from the M007 haplotype and likely arose within the region (Ruiz-Arce et al 2020). Another study by Nikolouli (2020) corroborates the link between the European continent and Central America and shows clear clustering of four European populations with four Central American populations, based on eight microsatellite markers. Additionally, a study by Karsten et al (2015) showed that Guatemala was likely colonized from Greece.…”
Section: Central Americamentioning
confidence: 56%
See 2 more Smart Citations
“…Two of the private haplotypes (M005 and M008) for the region only differed by two and three bases respectively from the M007 haplotype and likely arose within the region (Ruiz-Arce et al 2020). Another study by Nikolouli (2020) corroborates the link between the European continent and Central America and shows clear clustering of four European populations with four Central American populations, based on eight microsatellite markers. Additionally, a study by Karsten et al (2015) showed that Guatemala was likely colonized from Greece.…”
Section: Central Americamentioning
confidence: 56%
“…We caution the reader to consider that while diversity can support colonization time estimates, it is best interpreted together with other information such as historical reports. This work, together with the contribution by Nikolouli (2020), who used eight microsatellite loci, the work by Karsten et al (2015) and the more recent study by Ruiz-Arce et al (2020) who have both used mitochondrial DNA sequencing methods, render the most current view on medfly genetic diversity, geographic genetic structure and invasion pathways. Although we consider the current dataset as an informative instrument for investigating medfly invasion history, we note that it will benefit from resampling of populations and new collections to stay relevant in the future.…”
Section: Australiamentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial strains isolated from stable microbial communities of wild individuals can be provided to mass-reared insects as supplements, in an attempt to replicate the natural microbiome and improve fitness and mating success [ 5 , 6 , 7 ]. Studies dealing with tephritid microbiomics use either samples from laboratory colonies [ 8 , 9 , 10 , 11 , 12 , 13 ] or wild populations [ 10 , 14 , 15 , 16 , 17 , 18 ], which are generally characterized by higher microbial diversity compared to laboratory strains [ 10 , 19 ]. Therefore, it is important to identify and exploit this large portion of diversity, but also to determine how it is affected by the geographical isolation of wild populations.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with previous analyses of medfly microbiomes made using culture-based methods (Behar et al 2005;Behar et al 2008a;Behar et al 2008b;Behar et al 2009a). The picture may be more complex, however, as one recent next-generation sequencing study did not isolate Klebsiella in medfly microbiomes from wild populations (Malacrinò et al 2018), and another identified possible geographic or host-genetic structure links with bacterial dominance (with samples from Greece being dominated by Klebsiella spp) (Nikolouli et al 2020).…”
Section: Discussionmentioning
confidence: 99%